2007
DOI: 10.1149/1.2737660
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Structure Effects of Ring-Type Siloxane Precursors on Properties of Plasma-Polymerized Porous SiOCH Films

Abstract: Physical and chemical properties of plasma-polymerized SiOCH films were investigated using ring-type siloxane monomers with several kinds of side-chain chemicals, and a design principle of the material and plasma-process was derived to obtain a porous SiOCH film of k Ͻ 2.5 with sub-nanometer-scaled porous structure framed by the original ring siloxane backbone. Here, the backbone siloxane structure is fixed as a six-membered Si-O ring of the 0.35 nm, and no progen gas and no post-cure-process were utilized. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 18 publications
(17 reference statements)
0
24
0
Order By: Relevance
“…Simultaneously, the absorption intensity of the Si-H bond increased, as deposition temperature was increased. 23 In addition to infrared analysis, the compositions of SiC x N y films deposited at various deposition temperatures and their relative ratios to Si were quantified by XPS. These are summarized in Table II.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, the absorption intensity of the Si-H bond increased, as deposition temperature was increased. 23 In addition to infrared analysis, the compositions of SiC x N y films deposited at various deposition temperatures and their relative ratios to Si were quantified by XPS. These are summarized in Table II.…”
Section: Resultsmentioning
confidence: 99%
“…The N/Si ratio of the SiC x N y films decreased from 0.46 at 25 • C to 0.25-0.23 for deposition temperature between 100 • C and 400 • C. In contrast, their respective C/Si ratio decreased from 0.86 at 25 • C to 0.7-0.81 at T ∼100-300 • C and then there was a more radical decrease to 0.29 at a deposition temperature of 400 • C. This implied that during the deposition of SiC x N y film at 400 • C by PECVD, the desorption of CH x bonds may occur simultaneously, due to a pyrolysis process, which resulted in the rearrangement of the films' structure and the subsequent formation of dense SiC x N y films. 23 In addition to the XPS results, Figure 4 shows the position of the absorption band of N-Si-N in SiC x N y films deposited by PECVD at various temperatures, as measured by FT-IR analysis. At temperatures ≤200 • C, the Si-N absorption band was centered at 1047-1048 cm −1 and still displayed the characteristics of cyclic N-Si-N. As the deposition temperature was raised to 300 and then 400 • C, the Si-N absorption band was downshifted to 1043 and 1038 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Since there is little work on porous SiC x N y films, the pore sizes of asdeposited SiC x N y films in this study were compared to PECVD porous SiCOH films prepared using single precursor [12,13] and/or conventional approach using a precursor and an oxidant [26] The pore sizes in our study were found to be larger than SiCOH films prepared using single precursor [12,13]. Tada et al [12] reported PECVD porous SiOCH films with pore sizes ranging from 0.39 to 0.66 nm using a ring-type siloxane precursor with both of the vinyl and the alkyl side-groups at 350°C and under high pressure and low-power plasma condition to preserve the original ring-type chemical structure. C. H. Lo et al [13] reported SiCOH film prepared by using octamethylcyclotetrasiloxane (OMCTS) and pore diameter 0.74-0.76 nm for the matrix structure and 0.6-0.7 nm for big cages.…”
Section: Resultsmentioning
confidence: 99%
“…To further reduce the dielectric constant of silicon carbonitride materials, the primary approach is to reduce the film density, in addition to the continued increase of C/Si ratio. A similar approach has been demonstrated for low-k SiC x O y interlayer dielectric films by using single precursors with volumic cyclic structures, such as a 6, 8, or 10-membered Si-O ring [12,13] to introduce intrinsic and induced porosity for lowering the film's density.…”
Section: Introductionmentioning
confidence: 98%
“…Meanwhile detection of such groups in pristine low-k materials is extremely important because sp 2 carbon based residues (conjugated carbon polymers and amorphous carbon) are conductive and therefore they can be the reasons of high leakage current and low breakdown voltage in the integrated materials. Generally such residues can be detected by Raman spectroscopy [16] but application of these measurements for thin low-k films is quite challenging. Eslava and Marsik developed a method for detection of porogen residue from UV absorption spectra.…”
Section: Resultsmentioning
confidence: 99%